Tsunami in the Collective Memory: A Reception Study of the Visitors of Tsunami Memorials in Aceh, Indonesia - Muzayin Nazaruddin; Lana Senja Indah (Department of Communications, Universitas Islam Indonesia, 2021)
Disaster tourism could be defined as tourism practices based on certain disasters, both natural and cultural, which happened in the past. It melts the enjoyment and trauma, when people come and enjoy the monument of disaster or damaged place caused by a disaster. Thus, many questions arise: why do people come as tourists to disaster artefacts? How do people make meaning of the disaster artefacts? The paper examines this question, taking the visitors of Tsunami Museum, PLTD Apung Monument, and Kapal Tsunami Lampulo as study cases. The paper aims to describe the meaning of disaster tourism activities constructed by the visitors of these three memorials. The broader purpose of the study is to understand why and how people enjoy the disaster tourism destinations. The paper is based on qualitative research done in these three memorials in Aceh, Indonesia. The fieldwork to collect primary data was conducted in three months in 2015 and another three months in 2017, optimizing in-depth interviews and observations. The study concludes that disaster tourism activities are closely related to individual and collective memory. The Acehnese or the outsider, who is deeply related to the place or has direct experience of the tsunami, construct the meaning of their activities as remembering and recreational activities, which is closely associated with their inner level of memory. While the Indonesian and foreigners who do not have firsthand experience of the disaster construct the meaning of their visits as educational and recreational activities, which is related to the collective memory of the 2004 tsunami. Thus, the study confirms some previous studies that have emphasized that disaster tourism could have different roles and change its function to suit visitors' needs.Â Keywords: disaster tourism, collective memory, Tsunami Museum, PLTD Apung Monument, Kapal Tsunami Lampulo